Organizational Support and Justice Effects on Nurses’ Affective Commitment Mediated by Work Engagement - Ira Enda Ariani; Intan Silviana Mustikawati; Tjipto Rini; Varinder Singh Rana (Digital Innovation : International Journal of Management, 2026)
Employee affective commitment is a critical factor for workforce retention and service quality in healthcare organizations, particularly among nurses who represent the largest professional group in hospitals. Kemayoran X Hospital has experienced persistently high nurse turnover rates, indicating potential deficiencies in affective commitment. This study aimed to examine the influence of perceived organizational support and organizational justice on nurses’ affective commitment, with work engagement serving as an intervening variable. A quantitative cross-sectional design was employed, involving 125 staff nurses at Kemayoran X Hospital selected through purposive sampling. Data were collected using structured self-administered questionnaires distributed via Google Forms and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results demonstrated that perceived organizational support, organizational justice, and work engagement simultaneously exerted a significant effect on affective commitment. Furthermore, perceived organizational support and organizational justice showed significant positive effects on work engagement, which in turn significantly influenced affective commitment. Mediation analysis confirmed that work engagement partially mediated the relationships between perceived organizational support and affective commitment, as well as between organizational justice and affective commitment. These findings indicate that nurses who perceive fair treatment and strong organizational support are more likely to be engaged in their work and emotionally committed to their organization. In conclusion, strengthening organizational support systems, ensuring fairness in decision-making processes, and fostering work engagement are essential managerial strategies to enhance nurses’ affective commitment and reduce turnover in hospital settings.